Can initial trust boost intention to purchase Ayurveda products? A theory of consumption value (TCV) perspective. (3rd April 2022) - Chakraborty, Debarun; Siddiqui, Mujahid; Siddiqui, Aaliyah
Abstract: The demand for Ayurveda products has been increasing over the last decade, and consumption values are critical in understanding the driving forces behind the success of these products. This study examines an initial‐trust–mediated model using theory of consumption values (TCV) to predict consumer's intention to purchase Ayurveda products. The conditional, functional, emotional, epistemic, and social values in the TCV were used to build an initial‐trust–mediated model. The proposed model was analyzed using a sample of 440 usable responses. The outcomes revealed that the five consumption values used in the model influenced initial trust. Intention to purchase Ayurveda products was found to be influenced by the four consumption values, except social values. Initial trust strongly mediated the effect between consumption values and intention to purchase Ayurveda products. This study provides theoretical, practical, and managerial implications for marketers and other professionals in the natural, eco‐friendly, and green products sector.